A Pharmacological Overview and Recent Patent of Triazine Scaffold in Drug Development: A Review - Dubey, Pragya; Pathak, Dharam Pal; Chauhan, Garima; Ali, Faraat (Current organic synthesis, 2025)
The triazine moiety holds a special and very important position in the field of medicinal chemistry owing to its enormous biological and pharmacological potential. Over eras, triazine scaffolds have been investigated for synthesizing novel molecules that may be used for the treatment of different types of pathological conditions, such as infections, cancer, inflammation etc. A vast number of lead molecules have been established from the triazine moiety. The triazine fused with numerous heterocyclic rings, such as pyrrole, benzimidazole, indole, imidazole, carbazole, etc., have formed various bicyclic with pharmacological actions. The triazines display a wide range of activities, and synthesizing various marketable medicines that hold triazine moiety has made the attention of chemists worldwide grow over the years in the moiety. In this review article, the commercially available compound containing triazine has been presented, and an attempt has been made to collect the works reported, mostly in the past decade, by numerous scientists, related to the structural differences amongst the triazine analogues giving antitumor, and antimicrobial and other activities. The objective of this review article was to outline the current information on triazines and their derivatives with respect to their biological potential and various pharmacological activities. The summary of this review article would be helpful and describe the function and activity of the moiety to bring up-to-date the scientists working in the direction of designing and synthesising novel lead molecules for the treatment of different types of disease with the current molecules that have been synthesized from the triazine scaffold.
Keywords: antimalarial; Humans; anti-HIV; antimicrobial; Triazines; Antineoplastic Agents; Anti-Infective Agents; antiinfekční látky; lidé; zvířata; toxicity; triazine.; molekulární struktura; vyvíjení léků; Patents as Topic; Molecular Structure; Anti-cancer; triaziny; patenty jako téma; antiviral; protinádorové látky; cell line; Animals; Drug Development